Blackening graduate school: a study on the permanence of black students (PerCursos, 2026)
Admission to higher education is characterized as the main mechanism for access to scientific knowledge, and affirmative action policies as reparatory measures contribute to making this access more equitable for the black population. The aim of this article is to provide evidence of a study into the interfering factors and strategies for black quota students to remain in the Stricto Sensu Postgraduate Program at the Federal University of Mato Grosso, with entry through affirmative action policies as the basic aspect. The theoretical-methodological framework is based on references that interface with studies on Ethnic-Racial Relations Education, Black Feminism and Higher Education Policies. This is a qualitative, bibliographical, documentary and exploratory study. We believe, therefore, that entry to postgraduate studies does not guarantee quality completion, and that it is necessary to analyze the factors involved in remaining at this level of education.
Keywords: black students; admission; permanence; postgraduate stricto sensu; affirmative action policies